Dampak Tekanan Ketaatan, Pengetahuan, dan Pengalaman Auditor Terhadap Audit Judgment - Lambok DR Tampubolon (STIE Indonesia Banking School, 2018)
The purpose of this research is to examine the effect of auditor compliance, knowledge and experience on audit judgment. The data used in this study is primary data by distributing questionnaires to accounting firms domiciled in DKI Jakarta. From a sample of 17 accounting firms in DKI Jakarta and 100 respondents, this research shows that: compliance pressure and auditor knowledge have a positive effect on audit judgment, otherwise, auditor experience has no effect on audit judgment.